Spin Dynamics of Polarised Fermi-liquid 3He - Nyman, Robert Andrew (2003)
The spin-dynamics of Fermi-liquid helium-3 in pure form and in its mixtures with helium-4 are considered in this thesis. A linearised model of the spin dynamics is developed from Leggett's equation of motion, including spin-diffusion, the Leggett-Rice spin-rotation effect and cylindrical boundary conditions . The equations are solved using a matrix formalism, allowing simulation of FIDs, NMR spectra and spin-echoes. The boundary conditions are shown to cause deviations of spin-echo amplitude and phase from the predictions of Leggett and Rice, for realistic experiments. The model is extended to include the demagnetising field (dipolar field) due to the magnetisation of the sample itself. Simulations show that, when the demagnetising field is strong, spectral clustering is present and sharp peaks are observed in the NMR spectrum.